PENGARUH INFORMASI DIGITAL DENGAN MENGGUNAKAN APLIKASI PLATFORM DIGITAL TERHADAP PENJUALAN UMKM - Muasir Pagan (Journal Accounting International Mount Hope, 2023)
This research aims to find out how much influence social media FB,WA and instagram on sales turnover of Dayrini_shop Singaraja and (2) to know the influence of social media Facebook,WA, and Instagram on sale turnover. The object in this study is a clothing and accessories store “Dayrini Shop”.The data collection technique used through observations in the Clothing and Accessories Shop “Dayrinini Shop” as well as interviews with the owner of the Clothes and accessory store “ Dayrini shop” The results of this research show that the COVID-19 pandemic has a great impact on the business world especially small.With the existence of the Covid-19 Pandemic, the clothing store and accessories “Dayri Shop” Singaraja felt a significant change in its sales turnover.So Dayrin Shop used social media FB,WA and Instagram for advertising media and increased its sales omet.Dayrinin Shop felt the influence of Social Media, FBWA, Instagram and on the sales of clothes & accessories in “Dayríni Shop”.Social media, FBVA and Instagram had a positive influence on the Sales Volume of Packages and Accessory in the “Dayrim Shop” singaraja